Polymorphism in the Androgen Biosynthesis Gene (CYP17), a Risk for Prostate Cancer: A Meta-Analysis. Issue 5 (September 2020) - Effah, Clement Yaw; Wang, Ling; Agboyibor, Clement; Drokow, Emmanuel Kwateng; Yu, Songcheng; Wang, Wei; Wu, Yongjun
Gene polymorphism is one of the few factors that increases the risk of prostate cancer. T to C substitution in the 5' promoter region of the CYP17 gene is hypothesized to increase the rate of gene transcription, increase androgen production, and thereby increase the risk of prostate cancer. Nevertheless, the inconsistencies originating from studies on CYP17 polymorphism and prostate cancer prompted this meta-analysis, to decipher the association between CYP17 polymorphism and prostate cancer. Most case-control studies addressing CYP17 polymorphism and prostate cancer were exhaustively searched from Web of Science, Google Scholar, and PubMed. The various genotype distributions as well as the minor allele distributions were retrieved. Pooled odds ratios ( OR s) with their 95% CI and estimates of the Hardy–Weinberg Equilibrium were calculated. Analyses were performed using the RevMan v.5.3 software and SPSS v.21. There was high-pooled heterogeneity ( I 2 = 87.0%, OR = .42, CI [.39, .45], and p < .001) among the A2 versus A1 allele. With the per-allele model (A2 versus A1), ethnicity was a major risk factor to prostate cancer, with Asians recording the highest risk ( OR = 12.61, 95% CI [8.77, 18.12]). From the genotype models, A1/A1 versus A2/A2 ( OR = 3.02, 95% CI [2.65, 3.44]) and A1/A2 versus A2/A2 ( OR = 4.39, 95% CI [3.86, 5.00]) were all significantly associated with prostate cancer. Although some genotype models were associated with the risk of prostate cancer, we should be mindful when interpreting the results of this study because of the limited number of studies and the small sample size used.